Friends With Benefit Dalam Perspektif Pertukaran Sosial Di Kalangan Mahasiswa Kota Denpasar - Putri, Rismalia Anindra; Nugroho, Wahyu Budi; Pramestisari, Nyoman Ayu Sukma (Lenggogeni Data Publishing, 2024)
This research focuses on the phenomenon of friends with benefits (FWB) among students in Denpasar City. The purpose of this study is to analyze and explain the Friends With Benefits (FWB) in the perspective of social exchange. The method used in this research is a qualitative approach with descriptive-explanatory type. The theory chosen as a scalpel in analyzing this research is the social exchange of George C Homans. The results show that the main motivations for individuals to engage in FWB are sexual fulfillment, physical attraction, and a sense of comfort without pressure to build a long-term commitment. Supporting factors include mutual trust, open communication, and a shared understanding of boundaries and expectations in the relationship. Furthermore, the meaning of FWB among students in Denpasar City is seen as a form of ordinary relationship in social interaction which is considered not a negative thing. In the social exchange perspective, FWB relationships are seen as transactions in which both parties gain benefits with minimal risk. Abstrak Penelitian ini berfokus pada fenomena friends with benefits (FWB) di kalangan mahasiswa Kota Denpasar. Tujuan penelitian ini adalah Menganalisis dan memaparkan terkait Friends With Benefits (FWB) dalam perspektif pertukaran sosial. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis deskriptif-eksplanatif. Teori yang dipilih sebagai pisau bedah dalam menganalisis penelitian ini adalah pertukaran sosial dari George C Homans. Hasil penelitian menunjukkan bahwa motivasi utama individu untuk terlibat dalam FWB adalah pemenuhan kebutuhan seksual, ketertarikan fisik, dan rasa nyaman tanpa tekanan untuk membangun komitmen jangka panjang. Hal-Hal pendukung yang ditemukan termasuk adanya rasa saling percaya, komunikasi yang terbuka, serta pemahaman bersama mengenai batasan dan harapan dalam hubungan tersebut. Lebih lanjut, pemaknaan FWB di kalangan mahasiswa di Kota Denpasar dipandang sebagai bentuk hubungan biasa dalam interaksi sosial yang dinilai bukan suatu hal yang negatif. Dalam perspektif pertukaran sosial, hubungan FWB dipandang sebagai transaksi di mana kedua belah pihak memperoleh keuntungan dengan risiko minimal. Kata kunci: friends with benefits, pertukaran sosial, mahasiswa